2015
DOI: 10.1002/aur.1524
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Cognitive Characteristics Associated with Mathematics Problem Solving in Adolescents with Autism Spectrum Disorder

Abstract: Mathematics achievement in autism spectrum disorder (ASD) has been understudied. However, the ability to solve applied math problems is associated with academic achievement, everyday problem-solving abilities, and vocational outcomes. The paucity of research on math achievement in ASD may be partly explained by the widely-held belief that most individuals with ASD are mathematically gifted, despite emerging evidence to the contrary. The purpose of the study was twofold: to assess the relative proportions of yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 74 publications
(114 reference statements)
7
50
0
2
Order By: Relevance
“…Assouline et al (2012) found that in children with high IQ and ASD, working memory is associated with reading and written language. This result was however not replicated by Oswald et al (2016) as they did not find this relation when IQ and test anxiety were accounted for. Spaniol et al (2017) found that attention training (CPAT) significantly improved academic performance (maths, reading comprehension and copying text) in children with ASD, showing the importance of attention in many academic areas.…”
mentioning
confidence: 81%
“…Assouline et al (2012) found that in children with high IQ and ASD, working memory is associated with reading and written language. This result was however not replicated by Oswald et al (2016) as they did not find this relation when IQ and test anxiety were accounted for. Spaniol et al (2017) found that attention training (CPAT) significantly improved academic performance (maths, reading comprehension and copying text) in children with ASD, showing the importance of attention in many academic areas.…”
mentioning
confidence: 81%
“…We suggest that other academic domains, such as mathematics, could be teached in the same way. Indeed, a recent study showed that the strongest predictor of math problem solving was perceptual reasoning, which is a non-verbal cognitive skill (Oswald et al, 2016 ). Interestingly, the ability to solve applied mathematical problems is associated with everyday problem-solving abilities and vocational outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…Building on anecdotal (Baron-Cohen et al, 2007) and experimental accounts of savant skills in ASD (Howlin, Goode, Hutton, & Rutter, 2009), several studies have identified a subgroup of children with ASD who show relative strengths in math abilities (Chiang & Lin, 2007;Jones et al, 2009;Wei et al, 2015) that is distinct from a large, majority subgroup that shows average math abilities. More recent studies of individuals of ASD, however, have shown a high degree of variability in math skills, and suggest that weaknesses in math skills may be more prominent than giftedness in this population (Keen, Webster, & Ridley, 2016;Oswald et al, 2016;Titeca, Roeyers, Loeys, Ceulemans, & Desoete, 2015). A critical gap in this literature is an understanding of whether children with ASD show a unitary pattern of strengths and weaknesses across multiple mathematics subtests, including calculation and problem solving/reasoning, or whether heterogeneity in the ASD population is manifested by distinct subgroups of children with consistent profiles of mathematical abilities.…”
Section: Introductionmentioning
confidence: 96%